Fertilizer aerobic?fermentation equipment coordination air cycle individual layer formula aeration equipment - Xiong Liyin (2016)
The utility model discloses a fertilizer aerobic?fermentation equipment coordination air cycle individual layer formula aeration equipment, it is become by aerated conduit, air pump, the individual layer formula aeration nest of tubes, this fertilizer aerobic?fermentation equipment coordination air cycle individual layer formula aeration equipment is used for biological organic substance's aerobic?fermentation to handle, sets up in the circulation system of the multilayer formula aeration equipment of bobbin base portion, and the organic substance fermentation can be provided and sufficient aerobic conditions need be kept, this fertilizer aerobic?fermentation equipment coordination air cycle individual layer formula aeration equipment simple structure, auxiliary assembly is few, and convenient operation can realize full mechanized?operations, can adjust the air demand size, air feed to the bottom of material because air proportion is lighter, enables the air and constantly upwards emits, makes fermentation ma